A prospective survey to determine the general awareness and knowledge on COVID vaccinations among general public attending the vaccination clinic under a tertiary care hospital - Prasanna, Preetha; Veepanattu, Pranav; Edathadathil, Fabia; Babu, Binil; Ayyappan, Ajitha; Sundaram, Rejitha P.; Mohan, Mahitha; G. K., Arya; Sreedevi, Aswathy; K. V., Beena; Moni, Merlin; Sathyapalan, Dipu Thareparambil (International Journal Of Community Medicine And Public Health, 2022)
Background: The global impact of COVID pandemic has been unprecedented and had expedited the urgent need of mass vaccination especially in a densely populated country like India. Sustained efforts in strategies for increase the vaccination campaigns are essential at the community level to address the acceptance of vaccines. The perception of public understanding on COVID vaccinations would help healthcare professionals advise the public on vaccination and guide policy decisions. The aim of the study was to discover knowledge gaps related to various aspects of COVID vaccination among the general population and enhance awareness that improves the vaccination practice. Methods: A semi structured questionnaire was administered exploring the knowledge and awareness of public was conducted in a tertiary care centre located in southern part of India. The study participants were contacted during the time of vaccination. The key domains we collected from our survey included general perception on vaccines, knowledge on vaccine practice, vaccination practices on special population, vaccine specific knowledge and vaccine related socio-cultural factors on vaccinations. Results: Valid and complete responses were obtained from 4471 participants, among this majority were female participants (61.04%) with the median age of 36 years. Majority of the participants had a belief that vaccines are effective 3415 (81.8%) for preventing COVID-19. Conclusions: Vaccination campaigns must consider strong public participation and contextually relevant communication tactics for the better acceptability. Furthermore, we need a targeted capacity building initiative with more emphasis towards vulnerable populations to be implemented on vaccination.